Can mouth washes containing chlorhexidine 0.12% be used as synonym of a water solution of chlorhexidine 0.12%? - Suffredini, Ivana Barbosa [UNESP]; Coury Saraceni, Cintia Helena [UNESP]; Collantes Diaz, Ingrit Elida [UNESP] (Univ Sao Paulo, Conjunto Quimicas, 2015)
Chlorhexidine digluconate (CHX) is a gold standard drug in dentistry and is widely used as a reference in both in vitro and in vivo experiments. Due to ease of access, mouth washes containing CHX 0.12% are used as a substitute for aqueous CHX 0.12% solution in laboratory experiments. Additionally, it is well known that for product flavor purposes, volatile compounds are added to mouth washes formulations. Volatiles added to CHX 0.12% may improve wash's antibacterial ability. Volatiles add potency to the mouth wash formulation. Compared with an aqueous CHX 0.12% solution, it is proposed that CHX solutions and Periogard(R) would have antimicrobial activity. Antimicrobial activity was assessed in the present study via disk diffusion assays against Streptococcus mutans, Streptococcus sanguinis and Escherichia coli. Periogard(R) showed a significantly higher antibacterial activity in relation to CHX 0.12% (p<0.05) and a similar activity in relation to CHX 1% (p>0.05). Periogard(R) volatiles were analyzed by gas-chromatography/mass spectrometry (GCMS) and the presence of antibacterial menthol, menthone, isomenthol, menthyl acetate, trans-anethol and eugenol was verified. Finally, the use of Periogard(R) as a synonym of CHX 0.12% must be avoided, because its antibacterial activity is closely related to CHX 1%.
Keywords: Mouth washes/evaluation; Periogard (R); Chlorhexidine; Antimicrobials/mouth use/evaluation